Computer simulation of dispersion and combustion p rocesses of liquidfuels at high turbulence - Аскарова, А.; Болегенова, С.; Гороховский, М.; Туякбаев, А.; Оспанова, Ш.; Нугыманова, А.; Манабаева, Р. (Recent Contributions to Physics, 2016)
Numerical research of burning of liquid fuels is a complex challengeof thermo physics as demands the accounting of a large number of thedifficult interconnected processes and the phenomena. Therefore compu-ting experiment becomes more and more important element of researchof processes of burning and design of various devices using burningprocess. In work the mathematical model and the main equations de-scribing process of burning of liquid fuels at high turbulence is stated.Research of processes of disintegration and dispersion depending onpressure and an initial lot of injection in the combustion chamber for twotypes of liquid fuel is conducted: octane and dodecane. As a result of themade computer experiments dependences of the maximum temperatureon pressure were received, , distributions of carbon dioxide from a lot ofinjection, distribution of drops on radiuses and temperature fields at theoptimum mode of burning